Método cuantitativo para determinar los grados de infestación de gregarinas en camarones marinos - Varela Mejías, Alexander (2025)
The determination of the degree of gregarine parasitosis in marine shrimp is performed using qualitative or semiquantitative methods, which are based on the observation of visual fields of prepared coprological samples. These methods are subjective and lack repeatability, so tests were conducted using an alternative method based on the review of the total amount of the sample processed, expressing the results as the content of parasitic agents per unit of intestine length analysed. The proposed method is simple and allows for the reduction of the randomness of the counts, which can be useful in cases where greater certainty of diagnostic results is required.